Analisis Karakteristik DAS Di Kota Pekanbaru Berbasis Sistem Imformasi Geografis Untuk Menganalisis Hidrograf Satuan Sintetik - Fatiha Nadia; Manyuk Fauzi; Ary Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
A physical characteristic of a river is specifically able to describ by the morphometry parameters of a watershed. One method avalaible to analyze the characteristics of river stream is by itilizing the Digital Elevation Model (DEM) data obtained from the satellite image. Then this is processed by the GeographicInformation System (GIS) in order to develop river network mapping. Watershed characteristic data can be used to calculate the flood discharge using synthetic unit hydrograph method. Flood discharge data is used in many fields of waterresource design such as drainage, dams, and many others. Syhntetic unit hydrograph is the most pratical and simple method analyze flood discharge at watersheds which are not measurable. The most popular type of HSS is Gama Iand Nakayasu method. The principle of unit hydrograph with one millimeter of direct runoff is used to determine the most appropriate synthetic unit hydrograph method to be applied in watershed. In the case study of Siak-sub-watershed,Nakayasu method provides better result with less than 5% of error value and HDRO value close to 1 mm.Key words: Watershed characteristic, GIS, Gama I, Nakayasu, DRO